Adaptation and Validation of the Moral Distress Scale-Healthcare Professionals in Latvia - Cerela-Boltunova, Olga; Paskova, Anna (Journal of Ecohumanism, 2024)
Moral distress occurs when an individual recognizes the ethically appropriate action in a given situation but is prevented from acting on it due to external factors. The MMD-HP represents a major update to the previously revised Moral Distress Scale (MDS-R). This tool was designed and refined to measure the extent of moral distress experienced by healthcare professionals when encountering ethical challenges. The adaptation and validation process was conducted in four phases, employing various psychometric measures to ensure the scale's consistency with the original study. Psychometric indicators used include Cronbach’s alpha, Pearson correlation, and confirmatory factor analysis, among others. The MMD-HP total score ranged from 4 to 207, with a mean score of 95.3 (SD 53.8) for n=12, 79 19 (SD 46.4) for n=48, and 115.7 (SD 75.1) for n=201. The overall Cronbach's alpha in each phase of our study ranged from 0.907 to 0.965 The Chi-square of the scale was 315.49 and χ²/df = 0.9. The CFI was 0.934, TLI 0.913, and NFI was 0.891. The RMSEA was 0.059 and SRMR 0.08. We determined that the Latvian version of the MMD-HP is valid and reliable for assessing moral distress among nurses in Latvia.